Autonomic correlates of lifetime suicidal thoughts and behaviors among adolescents with a history of depression. (19th April 2019) - Yang, Xiao; Daches, Shimrit; George, Charles J.; Kiss, Enikő; Kapornai, Krisztina; Baji, Ildikó; Kovacs, Maria
Abstract: Suicidal thoughts and behaviors (STBs) have been associated with emotion dysregulation and atypical responses to affective and stressful stimuli. To investigate the psychophysiology involved, we measured changes in respiratory sinus arrhythmia (RSA) and cardiac pre‐ejection period (PEP; indexing parasympathetic and sympathetic functioning, respectively) in response to stressful‐ and sadness‐eliciting laboratory probes. Our sample included adolescents with a history of depression and STBs ( n  = 177), adolescents with a history of depression but no history of STBs ( n  = 47), and healthy controls ( n  = 175). The outcome of interest was the most severe form of clinician‐rated STBs across the subject's lifetime. In partial support of our hypotheses, during the stressful task, adolescents with a history of depression and STBs did not evidence the RSA decrease that was exhibited by controls and displayed greater PEP shortening compared to ever‐depressed adolescents with no lifetime STBs. No group differences were found in either RSA or PEP reactivity to the sadness‐eliciting stimulus. As expected, severity of STBs was positively correlated with the extent of PEP shortening during the stressful task. The results suggest that adolescents with a history of depression and STBs experience blunted parasympathetic responses to stress along with compensatory efforts. Our findings contribute to a better understanding of STBs among youths and underscore that future studies should examine physiological risk factors for these psychopathological outcomes. Abstract : We investigated autonomic correlates of lifetime suicidal thoughts and behaviors (STBs) and addressed the spectrum of STBs (including the forms of STBs that have been generally ignored by researchers in this area). This study contributes to the relatively scant literature on physiological markers of STBs and is the first to report that sympathetic activity indexes severity of lifetime STBs. Our findings may help strengthen efforts at early identification and possible prevention of STBs.